Peran Guru dalam Minat Baca Siswa Kelas 1 SD Negeri Banyuajuh 6 Kamal Bangkalan - Urifatus Sa’diyah; Agung Setyawan (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
This research is motivated by the researcher’s observation which was conducted at 1 st grade, Elementary school student of Banyuajuh 6 Kamal Bangkalan, Reseacher foaund that there still student who get difficulties in following lessons well, this based on students interest in reading is still low. The focus of this researchis to find out the role of teachers in increasing students reading reading interest in Elementary School Student of Banyuajuh 6 Kamal Bangkalan and to find out the obstacles and efforts faced by teachers in increasing students interest in reading. This research uses descriptive qualitative research. The data collection technique is carried out through observation, interview and documentation. Data analysis is carried out by collecting data, reducing data and presenting data. While the validity of data is carried out by trianggulation consisting of technical trianggulation, source trianggulation and time trianggulation.The result of this research show that the teacher’s role increasing students interest in readingis carried out by reading activities at the beginning of learning literacy, studying in the library with direcht control and supervision by the class teacher, using innovative learning methodes and giving prizes/rewards to students who can read. The obstacles faced by teachers are the character of student who are difficult to talk and prefer to play in the class.